CRYPTOCURRENCY EXCHANGE. BITCOIN– RISKS AND OPPORTUNITIES - Dariusz Szydłowski; Bronisław Młodziejowski; Kamil Martyniak (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2022)
the article presents an outline of a virtual currency- cryptocurrency exchange and the possible risks and opportunities associated with it. The genesis of cryptocurrency was discussed on the example of bitcoin. The aim of the article is to present various aspects of functioning of bitcoin in association with the events influencing the growth of interest in it. The article presents the creation of bitcoin and the concept behind its creation. An analysis of the advantages and disadvantages of this cryptocurrency was carried out. Bitcoin as an entirely virtual currency, which is not subject to any state institution or central bank, requires much more trust from its users than traditional states’ currencies. Also, the method of storing bitcoins is far from traditional. The article also describes the technical steps for using said cryptocurrency.